(untitled) (Research, Society and Development, 2024)
Autism Spectrum Disorder (ASD) is a neurodevelopmental condition characterized by difficulties in social communication and the presence of restricted and repetitive patterns of behavior and interests, with wide variability in severity and clinical manifestations. In turn, physical exercise plays a role in promoting health, contributing to physical and mental well-being, in addition to preventing chronic diseases. Therefore, this study aimed to evaluate the effectiveness of physical exercise in treating ASD symptoms in pediatric patients. To this end, an integrative literature review was carried out, analyzing articles published between 2019 and 2024, available in the SciELO, VHL, PubMed, and EBSCOhost databases. In total, seven studies were included in the review. These trials showed the benefits of physical activities on the metabolic profile, executive function, motor skills, sleep quality, and cognitive function of children with ASD. The results point to a positive influence of different types of physical exercise on the psychomotor deficits associated with the disorder. However, the small sample size and limitations in the description of randomization methods represent obstacles to the reliability of the findings, highlighting the need for future studies with more robust samples.